Proceedings of the 19th ACM Conference on Computer-Supported Cooperative Work &Amp; Social Computing 2016
DOI: 10.1145/2818048.2819975
|View full text |Cite
|
Sign up to set email alerts
|

Taking Notes or Playing Games?

Abstract: This paper presents a detailed examination of factors that affect perceptions of and attitudes towards multitasking in video conferencing. We first report findings from interviews with 15 professional users of videoconferencing. Our interviews revealed the roles and potential link of technology and activity. We then report results from a controlled online experiment with 397 participants based in the United States. Our results show that the technology used for multitasking has a significant effect on others' a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…While multitasking during one's own work mostly impacts personal productivity, special consideration of multitasking during meetings is warranted, as this can additionally impact other colleagues and their productivity [31]. Past work has looked at how people engage in multitasking both during in-person meetings and presentations [6,30,31], as well as online collaborative activities, such as remote meetings leveraging subjective feedback or perceptions [45,62]. For example, in educational settings, the use of laptops during a lecture has been shown to have a negative impact on attention, where students tend to engage in activities such as web-surfng or emailing rather than activities related to the lecture [6,30].…”
Section: Multitasking During Meetingsmentioning
confidence: 99%
See 2 more Smart Citations
“…While multitasking during one's own work mostly impacts personal productivity, special consideration of multitasking during meetings is warranted, as this can additionally impact other colleagues and their productivity [31]. Past work has looked at how people engage in multitasking both during in-person meetings and presentations [6,30,31], as well as online collaborative activities, such as remote meetings leveraging subjective feedback or perceptions [45,62]. For example, in educational settings, the use of laptops during a lecture has been shown to have a negative impact on attention, where students tend to engage in activities such as web-surfng or emailing rather than activities related to the lecture [6,30].…”
Section: Multitasking During Meetingsmentioning
confidence: 99%
“…However, in other studies, people who multitask during in-person meetings report to do so in order to interleave other important activities as they peripherally pay attention to the meeting and engage only when relevant [31]. In online settings, both meeting related and personal multitasking are seen as ways people's attention could divert from the actual conversation, though multitasking on a single screen is considered more acceptable than when multitasking is happening on a diferent screen -often presumed to be unrelated to the meeting [45]. Similarly, a study on video-chats among teens found that boredom was the main reason why teens would multitask during a video chat, wherein they would engage in scrolling social feeds or play games [62].…”
Section: Multitasking During Meetingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such technologies do not facilitate eye contact between participants, and they allow individuals to be engaged in other tasks that are not perceivable to other participants. Video conferencing that does not facilitate the perception of eye contact reduces trust [3], and head movements away from the camera in video conferencing conversations tend to be perceived negatively, depending on how those head movements are interpreted [14]. In addition, without a shared context (e.g., a physical workspace), trust between co-workers can be negatively impacted [7].…”
Section: Trust In Isolationmentioning
confidence: 99%
“…First, since this study mimicked Washington et al’s (2014) research on formal and informal meetings, we did not focus specifically on virtual meetings (with or without webcams) or conference calls in which participants were located at remote sites. Although some work has been done on perceptions of multitasking during meetings (Marlow, van Everdingen, & Avrahami, 2016), more information is needed in order to understand student and professional perceptions of appropriate mobile phone usage in remote meeting settings.…”
Section: Implications and Future Researchmentioning
confidence: 99%